Dreams as a source of supernatural agent concepts - McNamara, Patrick; Bulkeley, Kelly (Frontiers in Psychology, 2015)
We present a theory of the creativity of dreams as well as psychopathology of religious delusions with respect to production of fundamental forms of religious cognition—specifically supernatural agent cognitions. We suggest that dream cognitions are particularly efficient at producing highly memorable and impactful experiences with supernatural agents because dreams involve three processes that are prerequisites for the generation of god concepts: 1) mental simulations of alternative realities, 2) theory of mind attributions to the extra-natural dream characters and divine beings and 3) attribution of ultimate value (exemplified by ‘good spirit beings’) and dis-value (exemplified by demonic monsters) to the supernatural dream characters. Because prefrontal cortex is deactivated during REM sleep agentic impulses and internally generated ideas are not reliably attributed to Self or dreamer. Instead an exaggerated degree of agency is attributed to these supernatural dream characters who are then embedded in stories in dreams and in myths of waking life which explain their supernatural abilities. These dream-based supernatural agents are salient characters that are processed in sleep-related memory systems according to rules of Lleweelyn’s AAOM model and therefore more easily remembered and reflected upon during waking life. When REM sleep intrudes into waking consciousness, as is the case with some forms of schizophrenia, religious delusions are more likely to emerge.